Interpretive Flexibility in Mobile Health: Lessons From a Government-Sponsored Home Care Program - Nielsen, Jeppe Agger; Mathiassen, Lars (JMIR Publications, 2013)
BackgroundMobile technologies have emerged as important tools that health care personnel can use to gain easy access to client data anywhere. This is particularly useful for nurses and care workers in home health care as they provide services to clients in many different settings. Although a growing body of evidence supports the use of mobile technologies, the diverse implications of mobile health have yet to be fully documented. ObjectiveOur objective was to examine a large-scale government-sponsored mobile health implementation program in the Danish home care sector and to understand how the technology was used differently across home care agencies. MethodsWe chose to perform a longitudinal case study with embedded units of analysis. We included multiple data sources, such as written materials, a survey to managers across all 98 Danish municipalities, and semistructured interviews with managers, care workers, and nurses in three selected home care agencies. We used process models of change to help analyze the overall implementation process from a longitudinal perspective and to identify antecedent conditions, key events, and practical outcomes. ResultsStrong collaboration between major stakeholders in the Danish home care sector (government bodies, vendors, consultants, interest organizations, and managers) helped initiate and energize the change process, and government funding supported quick and widespread technology adoption. However, although supported by the same government-sponsored program, mobile technology proved to have considerable interpretive flexibility with variation in perceived nature of technology, technology strategy, and technology use between agencies. What was first seen as a very promising innovation across the Danish home care sector subsequently became the topic of debate as technology use arrangements ran counter to existing norms and values in individual agencies. ConclusionsGovernment-sponsored programs can have both positive and negative results, and managers need to be aware of this and the interpretive flexibility of mobile technology. Mobile technology implementation is a complex process that is best studied by combining organization-level analysis with features of the wider sociopolitical and interorganizational environment.